Penta-helix “Desa Emas” As A Commitment to Accelerate Stunting Reduction in Sumenep Regency, East Java Province - Nuraini Fauziah; Qurnia Andayani; Septi Ariadi; Toetik Koesbardiati; Bayu Praharsena (Universitas Airlangga, 2022)
Desa Emas is Elimination for Stunting in the Village that focuses on action to catalyst the reduction of stunting that carried out in 18 district/city in East Java. This program is initiated requires cooperation in achieving the goals. Collaboration that actively involves various sectors is very important, especially using penta-helix strategy include government, college, community, media mass and business partners to commit the acceleration of the stunting reduction. This study aims to describe the implementation of the penta-helix strategy